2021
DOI: 10.1177/00910260211061824
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Interracial Differences in Turnover Intentions: The Mitigating Role of Pro-Diversity and Justice-Oriented Management

Abstract: Enhancing racial justice, equity, diversity, and inclusion are the core values of public administration and critical to the functions of public-sector strategic human resources management. However, very limited empirical research has delved into the interracial differences in public sector employees’ turnover intentions and its mitigating factors. Using the 2006–2017 Federal Employee Viewpoint Survey data, the present study aims to contribute toward filling this gap in the literature. The theoretical arguments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…Older meta-analytic evidence indicated racial differences in perceptions of procedural justice within organizations (r = -0.10) (Cohen-Charash & Spector 2001). Moreover, Chordiya (2021) recently examined racial differences in justice among US government employees using the annual Federal Employee Viewpoint Survey from 2006 to 2017. The sample included more than 3 million observations, and the results indicated significantly higher procedural justice ratings among White than racioethnic minority employees (average item d = 0.17).…”
Section: Synopsismentioning
confidence: 99%
“…Older meta-analytic evidence indicated racial differences in perceptions of procedural justice within organizations (r = -0.10) (Cohen-Charash & Spector 2001). Moreover, Chordiya (2021) recently examined racial differences in justice among US government employees using the annual Federal Employee Viewpoint Survey from 2006 to 2017. The sample included more than 3 million observations, and the results indicated significantly higher procedural justice ratings among White than racioethnic minority employees (average item d = 0.17).…”
Section: Synopsismentioning
confidence: 99%
“…More than 25% of all articles reviewed applied representative bureaucracy (or versions founded on it) as the conceptual framework. Effective programs promoting a diverse workforce can reduce minority turnover (Chordiya, 2022), while inclusive leadership practices can help promote diverse environments, particularly for indigenous persons (Alang et al, 2022). People want to work for organizations in which they can relate, and organizations prosper when employees are treated equitably (Ford, 2022).…”
Section: An Overview Of Themesmentioning
confidence: 99%
“…In a study of local government employees, Hassan [39] found that both distributive and procedural justice enhance job involvement and organizational identification and attenuate turnover intentions among state employees. More recently, Chordiya [40] found that federal employees who felt a sense of fairness in the distribution of outcomes and procedures for allocating outcomes were less likely to leave their current agency. Surprisingly, although considerable progress has been made, we still lack a comprehensive empirical understanding of the mechanism through which organizational justice influences employee voluntary absenteeism.…”
Section: The Impact Of Organizational Justice On Employee Voluntary A...mentioning
confidence: 99%